On Wiener’s Tauberian theorems and convolution for oscillatory integral operators - Castro, Luís Pinheiro de (2019)
The main aim of this work is to obtain Paley–Wiener and Wiener’s Tauberian results associated with an oscillatory integral operator, which depends on cosine and sine kernels, as well as to introduce a consequent new convolution. Additionally, a new Young-type inequality for the obtained convolution is proven, and a new Wiener-type algebra is also associated with this convolution.